2012
DOI: 10.1057/rm.2011.9
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of causal factors in unintentional dwelling fires

Abstract: We examine the causal factors involved in unintentional dwelling fire incidents within the Merseyside area of the North West region of the United Kingdom. The approach of all-subsets multiple linear regression was used to develop an unintentional dwelling fire risk model for the region. The risk model was based on data obtained from UK government agencies relating to causal factors iden tified by earlier published studies. In the region studied, mental health problems, disability and residents living alone wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Links between fire rates and single person households have been reported before [22,33], but previous research has not noted the influence of the age of individuals living alone. Those under 65, and in particular those in the 35-54 age bracket, appear to be an important group whose presence is strongly linked to higher rates of accidental dwelling fire.…”
Section: Correlationmentioning
confidence: 98%
See 1 more Smart Citation
“…Links between fire rates and single person households have been reported before [22,33], but previous research has not noted the influence of the age of individuals living alone. Those under 65, and in particular those in the 35-54 age bracket, appear to be an important group whose presence is strongly linked to higher rates of accidental dwelling fire.…”
Section: Correlationmentioning
confidence: 98%
“…People living alone and of working-age are known to have lower rates of economic activity than the general population, and to be more likely to smoke or drink [35]. With a considerable proportion of dwelling fires attributable to smoking material [2] or associated with drinking [20,33] this may be one mechanism linking the younger group to increased rates of fire. Indeed, there is good evidence that alcohol is an important factor in fire related deaths of those under 60 in particular [36].…”
Section: Correlationmentioning
confidence: 99%
“…When considering demographic and socio-economic factors, research has pointed to a number of significant correlations. First, fire incidents are more likely to occur in households where the occupant suffers from a disability and/or illness (Bain et al , 2002; Holborn et al , 2003; Maull et al , 2010; Smith et al , 2008; Taylor et al , 2012). Moreover, poor health and disability amongst the elderly further reduce the likelihood that they can escape during a fire (Harpur et al , 2014).…”
Section: Studying Fire Risk Behaviours In Homesmentioning
confidence: 99%
“…Moreover, poor health and disability amongst the elderly further reduce the likelihood that they can escape during a fire (Harpur et al , 2014). Second, studies have identified social deprivation as a significant factor in house fires (Bain et al , 2002; Chhetri et al , 2010; Duncanson et al , 2002; Mulvaney et al , 2008; Shai, 2006; Smith et al , 2008: Taylor et al , 2012). Third, research has shown that households with single occupants also appear more at risk of domestic fire incidents (Holborn et al , 2003; Smith et al , 2008; Taylor et al , 2012).…”
Section: Studying Fire Risk Behaviours In Homesmentioning
confidence: 99%
See 1 more Smart Citation